1989
DOI: 10.1200/jco.1989.7.2.214
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of Hickman/Broviac catheters and implantable ports in pediatric oncology patients.

Abstract: We prospectively studied the continuous function and complication rates of 286 central venous catheters consecutively placed in 264 children and young adults at a single institution over a 19-month period (median follow-up, 376 days). Externalized catheters (91 Hickman [H], 113 Broviac [B]) and implantable ports (n = 82) were compared for complications, including infection and thrombosis. The most frequent major complication of all catheters was infection, although the rates of infection varied with the durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
56
1
2

Year Published

1993
1993
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(72 citation statements)
references
References 20 publications
13
56
1
2
Order By: Relevance
“…[1,2]. Technological development in this area is ongoing, and two possible improvements over the classic venous port systems arc represented by the side entry access dual lumen port [3], and mini-port systems [4,5], Mini-port systems may cause less cosmetic damage and are propagated as a peripheral access system using the arm of the patient as implantation site.…”
Section: Port-systemementioning
confidence: 99%
“…[1,2]. Technological development in this area is ongoing, and two possible improvements over the classic venous port systems arc represented by the side entry access dual lumen port [3], and mini-port systems [4,5], Mini-port systems may cause less cosmetic damage and are propagated as a peripheral access system using the arm of the patient as implantation site.…”
Section: Port-systemementioning
confidence: 99%
“…Ports are accessed by means of a special needle through intact skin. In pediatric oncology patients, ports are associated with a lower rate of catheterrelated bloodstream infection than are Broviac/Hickman catheters [1][2][3][4].Although cure of bloodstream infections related to nontunneled vascular catheters generally requires catheter removal, we and others have found that ϳ75% of Broviac/Hickman catheter-related bloodstream infections are cured without catheter removal [3][4][5][6]. In contrast, there are limited data concerning the efficacy of antibiotic treatment of port-associated bloodstream infection without port removal.…”
mentioning
confidence: 99%
“…The most common and potentially severe acute sequelae are infection and thrombosis. 1 Of interest, a registry study designed to determine the incidence and characteristics of deep-vein thrombosis (DVT) among children in the general population identified the use of CVLs as the single most important predisposing factor for DVT. 2 Acute thrombosis of CVLs usually becomes evident by the inability to draw blood from or infuse products into the line, although there are reports of emergency presentations with pulmonary embolus, congestive heart failure, or superior vena cava syndrome.…”
mentioning
confidence: 99%